2021
DOI: 10.1080/00365521.2021.1901308
|View full text |Cite
|
Sign up to set email alerts
|

Patients with inflammatory bowel disease on immunosuppressive drugs: perspectives’ on COVID-19 and health care service during the pandemic

Abstract: Background and aims: Patients with inflammatory bowel diseases (IBD) have experienced changes to the routine management because of the SARS-CoV-2 pandemic. The aim of this study was to examine patients with IBD's adherence to the restrictions imposed by society and the hospital, worries and concerns regarding medical treatment and clinical follow-up under the pandemic. Methods: IBD patients (!18 years) at the outpatient clinic at Oslo University Hospital were included and answered a self-report questionnaire i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Subgroup analysis indicated a prevalence of 9.43% (95% CI − 13.86 to 32.73%; n = 10 studies) of COVID-19 among the patients with CD 26 28 , 34 , 35 , 45 , 46 , 73 , 76 , 84 and 8.58% (95% CI − 8.22 to 25.38; n = 10 studies) among those patients with UC 27 , 28 , 34 , 35 , 45 , 46 , 55 , 73 , 76 , 84 . This analysis indicated that, type of IBD was not a contributing factor to the heterogeneity as there was no change in the level of heterogeneity even after a subgroup analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analysis indicated a prevalence of 9.43% (95% CI − 13.86 to 32.73%; n = 10 studies) of COVID-19 among the patients with CD 26 28 , 34 , 35 , 45 , 46 , 73 , 76 , 84 and 8.58% (95% CI − 8.22 to 25.38; n = 10 studies) among those patients with UC 27 , 28 , 34 , 35 , 45 , 46 , 55 , 73 , 76 , 84 . This analysis indicated that, type of IBD was not a contributing factor to the heterogeneity as there was no change in the level of heterogeneity even after a subgroup analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, however, no GI symptoms were observed. This might be explained by the median age in our sample, which was higher than the median age in the metanalysis by Badal et al, even when adjusted to include only the pediatric patients (15 years [7][8][9][10][11][12][13][14][15][16][17][18] compared to 8 years [6][7][8][9][10]).…”
Section: Discussion/conclusionmentioning
confidence: 79%
“…Until the moment, the knowledge concerning the risk of COVID-19 in inflammatory bowel disease (IBD) patients, particularly pediatric IBD patients, is still scarce [ 8 , 9 ]. Recent studies seem to show that IBD patients are at no greater risk than the general population [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study focused upon mitigation techniques such as quarantine and avoiding in-person visits. 8 No data were obtained surrounding patient prioritization of research questions based on their fears. A second web-based survey on disease-related experiences of patients with IBD and concerns during the COVID-19 pandemic showed that 62% feared an increased risk of severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%